Relationships among the cervical mucus urea and acetone, accuracy of insemination timing, and sperm survival in Holstein cows - Beran, J; Stádník, L; Ducháček, J; Okrouhlá, M; Doležalová, M; Kadlecová, V; Ptáček, M (Animal reproduction science, 2013)
The objectives of this study were to evaluate the relationships among urea and acetone content in cows' cervical mucus (CM), its crystallization type (CT) and sperm survival (SS) after timed AI. Samples of CM were collected from 192 Holstein cows treated by Ovsynch(®) protocol. Analysis of the urea and acetone content for identification of the metabolic status, the arborization test for evaluation of insemination timing and the short-term heat test of SS for assessment of its suitability as a biological matrix were performed. The data set was analyzed by the GLM procedure using SAS(®). The results documented the existence of substantial differences in individual response to the Ovsynch(®) protocol causing insemination of 55.2% cows at an inappropriate time. The urea content was found as a possible indicator of a cow's metabolism and/or of insemination timing, concentrations of less than 500 mg/L corresponded (P<0.05-0.01) to the cows' expected response to timed AI. The greater the urea content, the greater the proportion of cows inseminated at an inappropriate time. Effects (P<0.05-0.01) of CT, urea and acetone content on SS were determined. The greatest values of SS were detected in cows with an expected response to precisely timed oestrus documented by the corresponding CT. Greater values of urea (>260 mg/L) and acetone (>5mg/L) negatively affected SS as well (P<0.05-0.01). The results confirmed that the accuracy of insemination timing can be affected by the metabolism intensity, just as CM quality directly influences sperm survival.
Keywords: Cattle; Animals; skot; Female; Insemination, Artificial; močovina; spermie; Sperm survival; Acetone; ženské pohlaví; Spermatozoa; cervix uteri; Reproduction; Time Factors; časové faktory; cervikální hlen; Cervix Mucus; Male; umělá inseminace; Cervical mucus; aceton; zvířata; mužské pohlaví; Cervix Uteri; Urea